Optimizing Capacity of a Hybrid Diesel-Solar PV-BESS on Nusa Penida Island Using a Load Following Approach - Enggar Bowo Suasono, Oktavianus; Husnayain, Faiz (International Journal of Computer and Information System (IJCIS), 2025)
Indonesia, as the world's largest archipelagic country, faces substantial challenges in achieving equitable energy access, particularly in remote regions. These areas are predominantly reliant on Diesel Power Plants (PLTD), which result in high operational costs, logistical complexities in fuel supply, and considerable carbon emissions. Despite these limitations, remote regions possess abundant renewable energy resources, particularly solar energy. However, the intermittency of solar generation due to weather fluctuations hampers its reliability as a primary energy source. To address these challenges, this study proposes the implementation of a hybrid energy system integrating Solar Photovoltaic (PV) systems and Battery Energy Storage Systems (BESS), supported by a load-following dispatch strategy and optimal capacity planning. The objective is to improve both the reliability and efficiency of the local power system. The study was conducted on Nusa Penida Island, specifically at the 20 kV Kutampi Substation, which is interconnected with the existing diesel power infrastructure. The methodology encompasses a comprehensive literature review, secondary data acquisition, manual system sizing, and simulation-based analysis. PV capacity potential was assessed using PVSyst software, while power flow and voltage simulations were performed for three operational scenarios: (i) existing diesel-only configuration (baseline), (ii) hybrid Diesel-PV-BESS configuration, and (iii) PV-BESS configuration without diesel generators. Power system simulations were carried out using a computer-based electrical analysis platform to evaluate the technical impact of integrating renewable energy into the local grid. Simulation results demonstrate that the integration of PV and BESS enhances voltage stability and ensures a more reliable energy supply. Furthermore, techno-economic analysis reveals that the hybrid Diesel-PV-BESS configuration yields the most favourable outcome, achieving a Levelized Cost of Energy (LCOE) of IDR 3,088 per kWh. These findings underscore the potential of hybrid renewable energy systems as a viable solution for sustainable energy development in remote island regions.